Illusory visual motion stimulus elicits postural sway in migraine patients - Imaizumi, Shu; Honma, Motoyasu; Hibino, Haruo; Koyama, Shinichi (Frontiers in Psychology, 2015)
Although the perception of visual motion modulates postural control, it is unknown whether illusory visual motion elicits postural sway. The present study examined the effect of illusory motion on postural sway in patients with migraine, who tend to be sensitive to it. We measured postural sway for both migraine patients and controls while they viewed static visual stimuli with and without illusory motion. The participants’ postural sway was measured when they closed their eyes either immediately after (Experiment 1), or 30 seconds after (Experiment 2), viewing the stimuli. The patients swayed more than the controls when they closed their eyes immediately after viewing the illusory motion (Experiment 1), and they swayed less than the controls when they closed their eyes 30 seconds after viewing it (Experiment 2). These results suggest that static visual stimuli with illusory motion can induce postural sway that may last for at least 30 seconds in patients with migraine.